Pivot : the art and science of reinventing your life - Markel, Adam (Atria Books, 2016)
"The successful CEO of the internationally renowned Peak Potentials--who has trained thousands of people to find new jobs, careers, and directions--shares his practical and inspirational program for reinventing yourself, whether you are out of work or want to change your professional trajectory. What would you do in your life if you knew you could not fail? That's the question answered in Pivot, a roadmap for embracing your true potential without abandoning your responsibilities or risking your future. As a transformational teacher and the CEO of Peak Potentials, which has trained more than one million people worldwide, Adam Markel can help you leap out of your comfort zone and into the destiny you've always dreamed of. Whether you are transitioning your career, or have been downsized, or believe that your true potential has yet to be fully tapped, Pivot is a guide to reinvention for anyone, at any age. With clear-eyed compassion and frank assessments, Adam shares the secrets that will guide you away from fear and toward a powerful new vision for your life. The uplifting stories, introspective prompts, clear step-by-step exercises, and energizing calls to action throughout this remarkable book will guide you through the process of personal and career transformation, from creating a vision and clearing space for change to building a supportive environment and establishing daily rituals that will regenerate your soul. Success and personal fulfillment are within reach! Program your internal GPS to a destination of your wildest imagination--all it takes to change your path is one right turn"--